Understanding Attitudes to Development. Public Perceptions of International Development and Support for Aid in Iceland: A Qualitative Enquiry - Júlíana Ingham 1959- (2013)
In March 2013 the Icelandic parliament endorsed the next four years of overseas development strategy involving substantial increases in the aid budget, rising from 0.21% of GNI in 2012 to 0.42% in 2016, aiming to reach the 0.7% international donor target by the year 2019. Successful and sustainable international development policies and budgets are believed to require a constituency for aid in donor countries. Can we therefore assume a base of public support and presuppose an understanding of the importance of development aid amongst the Icelandic public? Unlike many donor countries no formal research has been conducted in Iceland documenting public attitudes towards aid. This study aims to present an in-depth picture of public attitudes to, awareness of, and engagement with aid and development, and has the secondary aim of evaluating what type of development communication approaches best engage people in development issues. Using a qualitative mode of enquiry and analysing data provided by seventeen participants, a detailed picture of not just what the public thinks, but why they think it has been constructed. Although indicating generous public support for development in principle, the results reveal perceptions of development as humanitarian aid and uncover limited understanding of how long-term development works in practice. This information gap reinforces one-dimensional images of poverty in developing countries and engenders sceptical attitudes towards the effectiveness of aid. Although overwhelmingly motivated by moral factors, people perceive development messages to focus on charity and donations rather than justice and participation, creating a risk of disengagement with development issues in the long-term. The implications of this research call for a reframing of development messages, placing more emphasis on communicating long-term development challenges and encouraging more supporter involvement, with the aim of deepening the public’s understanding of the complexities of development and providing ...